O efeito do risco Brasil sobre os retornos do mercado imobiliário e o mercado em geral, e os determinantes macroeconômicos do preço de imóveis residenciais - Amorin, Anderson Luis Walker (2016)
The study of Brazilian real estate market, it s getting importance over time. In this sense the compression of how the Brazilian real estate market works, just like the relations between the investment options are important to investors to know better the risk of those assets. Thus, a Vector Autoregressive Model was used to analyze the short term relations between Brazilian real estate assets, general market and the Brazil Risk. The same way, was modeled an ordinary least square linear regression to identify the macroeconomic determinants of house price returns. The data used was for real estate investment trusts, the IFIX index, to real estate stocks was used the IMOB index, to the overall market we use the Ibovespa index and to represent the Brazil Risk, was used the EMBI+BR index. The research demonstrate an information transmission between the Brazil Risk and the financial assets of real estate market shows a positive relation with the overall market. Complementary to this, the returns of house properties prices had as macroeconomic determinants the interest rates and inflation index.